Speaker Identification Using Wavelet Packet Transform and Feed Forward Neural Network - Almashrgy, Mohamed Ali (2005)
It has been known for a long time that speakers can be identified from their voices. In this work we introduce a speaker identification system using wavelet packet transform. This is one of a wavelet transform analysis for feature extraction and a neural network for classification. This system is applied on ten speakers